Brandpreneurship-Based Business Development Strategy Using the SOAR Method in the Sultan Ayam Geprek Restaurant Business - Zul Aswar Bakri; Muhammad Rakib; Hajar Dewantara (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study aims to examine and formulate a business development strategy based on brandpreneurship using the SOAR approach at Sultan Ayam Geprek Restaurant in Makassar City. The research is motivated by the suboptimal management of brand identity and the implementation of branding strategies, despite the business having strong potential in terms of strategic location, distinctive taste, and customer loyalty. The study employs a descriptive qualitative method, with data collected through interviews, observations, and documentation involving the business owner, employees, and loyal customers. The findings reveal that the main strengths of the business lie in its unique taste, affordable pricing, and strategic location. However, there are notable weaknesses related to the inadequate management of brand identity and less effective branding strategies. On the other hand, opportunities arise from the increasing public interest in fast food and the growing use of digital media. Based on the SOAR analysis, a brandpreneurship-based development strategy is proposed, focusing on strengthening brand identity, enhancing branding efforts, optimizing digital marketing, introducing menu innovations, and improving customer experience.